Analysis of Finger Position During Two- and Three-Fingered Grasp: Possible Implications for Terminal Device Design - Maitland, Murray E.; Epstein, Molly B. (Journal of prosthetics and orthotics, 2009)
Analysis of human hand motion has been used in the past to justify theoretical designs of terminal devices. The current study assessed normal ranges of motion and finger positions during standardized grasp activities. Seated subjects (n=7) were asked to grasp simple geometric shapes, one at a time, using either two fingers or three fingers. The objects for this study were chosen based on their shape, size, and mass distribution. Small reflective markers were affixed to the fingers and hand. A six-camera motion analysis system was used to gather marker position data that was modeled as linked segments to calculate joint angles. Thumb position during two and three finger grasp of standard geometric objects was relatively constant using less than half of the available range of motion. Average thumb positions during grasp, across all subjects, were within a 20 degrees total range of motion. The index finger and long finger also used less than 50% of their available total range of motion. The largest variability for articular angular position during grasp was found in the metacarpophalangeal (MCP) joints of the index and long fingers. In comparison, the hook terminal device had a potential angular range of motion of 70 degrees of opening at a single hinge. The hook achieved a two- or three-point grasp depending on the object geometry relative to the contact surface. The modified hook had the same 70 degree opening as the hook but achieved contact with the object because of passive rotation of secondary articulations. Design criteria for prosthetic terminal devices used specifically for grasping activities might focus on specific aspects of hand motion to reduce complexity or cost of the device.